Fault-tolerant multilevel converter - Lim, Yuan Jun (Nanyang Technological University, 2022)
This report presents the design and control of an Active Nested Neutral-Point-Clamped (ANNPC) Converter with its fault-tolerant capabilities. The Active Nested Neutral-Point-Clamped Converter is a type of hybrid multilevel converter which can produce output voltages with a lower total harmonic distortion (THD) due to the reduction in the capacitor ripples, thus providing an improved power quality for the system. Various faults within the converter will be evaluated and discussed. Also, the ways to minimize its impact on the system for the converter to run normally by adjusting its control algorithm will be presented with simulation in Simulink/MATLAB.